The State of Paediatric Dialysis: Is the Story Different at Federal Medical Center, Asaba, South-South Nigeria? - Ezeonwu, Bertilla U; Ajaegbu, Obinna C; Joseph, Uzoma C Ajanwenyi; Achuzia, Blessing E; Ajanwenyi, Joseph N; Osim, Chinemerem; Origbo, Lazarus C; Onwuli, Rachael E (Indian Journal of Child Health, 2024)
Introduction: Dialysis is a type of renal replacement therapy (RRT) employed to maintain the excretory function of a failed kidney. Hemodialysis is the most common form of dialysis offered worldwide and in Nigeria and in this analysis, we compared our experiences with previously published studies on pediatric dialysis. Method: A retrospective observational case series study of a prospective clinical database of children admitted into the pediatric ward of Federal Medical Center, Asaba, South-South Nigeria, who accessed hemodialysis during their management in the Pediatric nephrology unit, from November 2016 to October 2022 (6 years). Results: There were 78 patients admitted and managed by the nephrology unit during the study period, 37.2% required RRT, and 69.0% accessed it of which 55% were females, 80% were adolescents, and 55% with Acute Kidney Injury (AKI). The median age at initiation of RRT was 12 years. Patients requiring hemodialysis (HD) for AKI were majorly those with nephrotic syndrome while most of those with chronic kidney disease (CKD) were of unknown etiology. All patients had multiple indications for HD but the most frequent was anuria. Patients with AKI were younger and pericardial effusion was a more common indication for HD in patients with CKD. The inpatient case fatality rate was 25% but the total including during the follow-up period was 50%. The presence of encephalopathy as an indication of HD was associated with an increased case fatality rate. Conclusion: Our RRT experience was comparable to other published works. The findings from this analysis underscore the need for nephro-prevention at all levels, as RRT is largely inaccessible and with fatal outcomes in our environment.